2018
DOI: 10.1155/2018/4258020
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Design Optimization of Aerial Vehicles: A Review of Recent Advancements

Abstract: The aim of this paper is to present the most common practices in multidisciplinary design optimization (MDO) of aerial vehicles over the past decade. The literature sample is identified through established internet search engines, and a stringent review methodology is implemented in order to ensure the selection of the most relevant sources. In this work, the primary emphasis is on the assessment of the state-of-the-art framework development strategies, while at a secondary level, the objective is to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 118 publications
0
17
0
Order By: Relevance
“…In the same review done by Papageorgiou et al [6], they found that 52% of the aerodynamics models used in MDO were reduced order models (Panel codes), 11% medium resolution (Euler Solvers or coarse CFD simulations) and 37% high resolution (Full CFD simulation).…”
Section: Aerodynamics and Stabilitymentioning
confidence: 98%
See 3 more Smart Citations
“…In the same review done by Papageorgiou et al [6], they found that 52% of the aerodynamics models used in MDO were reduced order models (Panel codes), 11% medium resolution (Euler Solvers or coarse CFD simulations) and 37% high resolution (Full CFD simulation).…”
Section: Aerodynamics and Stabilitymentioning
confidence: 98%
“…In a review conducted by Papageorgiou et al on the advancements in MDO of aerial vehicles [6] it has been shown that the mass estimation discipline is the second most common discipline when it comes to aerial vehicles design. This is evident since vehicle mass is pivotal to the aerodynamic and performance calculations, which will ultimately be one of the most influential variables in the optimization [7].…”
Section: Mass and Balancementioning
confidence: 99%
See 2 more Smart Citations
“…An often-overlooked challenge is graphical visualisation and its role in decision-making. A review article on the state of the art and common practices in MDO of aerial vehicles (18) identifies an increasingly important demand for frameworks with capabilities related to post-processing of optimisation results and design space visualisation in an efficient and intuitive way to better assist in the decision-making process. This shortage is even more severe in OUU due to the inherent increase in problem dimensionality.…”
Section: Introductionmentioning
confidence: 99%